2020
DOI: 10.3390/s20216285
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Power Spectral Densities and Phase Quantities Due to Processing of EEG Signals

Abstract: There has been a growing interest in computational electroencephalogram (EEG) signal processing in a diverse set of domains, such as cortical excitability analysis, event-related synchronization, or desynchronization analysis. In recent years, several inconsistencies were found across different EEG studies, which authors often attributed to methodological differences. However, the assessment of such discrepancies is deeply underexplored. It is currently unknown if methodological differences can fully explain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…As indicated, both APA1 and APA2 were more negative during stress than at rest and meditation which demonstrate that the right alpha power was reduced considerably more than the left alpha power during stress situation. These results are in line with the physiological expectations that increased cortical activity in the right hemisphere is associated with processing of negative emotions such as stress [16] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As indicated, both APA1 and APA2 were more negative during stress than at rest and meditation which demonstrate that the right alpha power was reduced considerably more than the left alpha power during stress situation. These results are in line with the physiological expectations that increased cortical activity in the right hemisphere is associated with processing of negative emotions such as stress [16] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
“…The EEG data computation starts by selecting the data from the four electrodes: two electrodes in the left-hemisphere (F3, Fp1), and two electrodes in the right-hemisphere (F4, Fp2) in reference to electrode Fz. For power spectral density (PSD) estimation, the Welch’s method, a nonparametric method which is a modified approach of Fast Fourier Transform (FFT) algorithm [33] was used to classify the signals based on frequency into five frequency bands: Delta (0.2 – 3 Hz), Theta (3 – 8 Hz), Alpha (8 – 13 Hz), Beta (13 – 30 Hz) and Gamma from 30 Hz and up. The alpha band power asymmetry between the left and right hemisphere was calculated using the equation in Table 2 .…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Our results support the claims made in the literature [33,48,68,69] that the automated ICA-artifact preprocessing pipeline offered substantial benefits by increasing consistency and efficiency for classifying artifacts or non-artifacts ICs. On the contrary, Alam et al [49] have found that the selection of artifact removal had distinct effects on the PSD calculation. However, the recent findings in Noor et al [40] showed that the artifacts rejection by the automatic continuous rejection and experts confirmation provided promising results in predicting TBI outcomes of specific frequency bands.…”
Section: Discussionmentioning
confidence: 95%
“…Artifacts in EEG signals might make interpretation difficult and lead to incorrect analytical judgments. Numerous algorithms and preprocessing pipelines have been developed to address the problem of artifact rejection in electrophysiological data [32,49,[63][64][65][66][67]. Each of these algorithms has its own set of strengths and focuses on a different area of artifact rejection than the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation